Design of Accounting Information System Raw Material Inventory At PT Warung Pasta With Software Microsoft Visual Basic 6.0 And SQL Server 2000 Bases Of Client Server (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
PT Warung Pasta located at Ganesha No. 04 Bandung, Phone. 022-2500416 is a manufacturing company moving on the culinary area. At the time of implementing the accounting records and updating the inventory of raw material to the company's use Microsoft Office Excel software. These problems result in ineffective and optimal performance of all divions of the company contained in the provider of information and reports required. From the matter above, the writer take the title "Design of Accounting information System Raw Material Inventory at PT warung Pasta with Software Microsoft Visual Basic 6.0 and MySQL Server 2000 Bases of Client Server".